Fibroid after Hysterectomy A Radiological Diagnostic Dilemma (Bangladesh Journal of Radiology and Imaging, 2026)
Broad ligament fibroids or extra-uterine leiomyomas are not common, that occurs in relation to the broad ligament. While in most cases broad ligament fibroids are asymptomatic, patients may present with pelvic pain or a palpable pelvic mass. The pain, when long standing, may be due to pressure effects on adjacent organs like bladder or ureter. We found a case as a broad ligament leiomyoma in a woman after a hysterectomy. The patient has come to us for routine checkup and ultrasound. Ultrasound, trans-vaginal sonogramand MRI scan was suggestive of possible parasitic leiomyoma. Laparotomy and removal of the mass, followed by histological examination confirmed leiomyoma. Extra uterine fibroid should be considered in the diagnosis of pelvic masses even after post-hysterectomy state.